Hattie's Visible Learning Evaluation Model in Learning Strategies and Publication of Scientific Work of IKIP Siliwangi Students - Suhud Aryana; Dida Firmansyah; Ratna Muthia (JLER (Journal of Language Education Research), 2024)
This research aims to evaluate the application of the Hattie's Visible Learning Evaluation Model in strategy learning and the publication of scientific work sat IKIP Siliwangi. Using quantitative and qualitative data analysis methods, this research analyze student responses to sixty aspects of assessment that cover various learning elements. The results of the research identified the aspects with the highest and lowest scores from each study program, namely Guidance and Counselling (BK) and Indonesian Language and Literature Education (PBSI). These results provide in-depth insight regarding significant factors in developing effective learning strategies and supporting the publication of student scientific work such as humor, teaching strategies teacher, credibility outdoor/adventure programmes, lecturer effect, lecturer subject matter knowledge, questioning, religious campus, feedback personality, mentoring computer-assisted instruction, lecturer-students relationships, drama/art programs, study skills, extra-curricular programs, dan classroom discussion. Meanwhile, less effective factors are of concern, such as parental involvement, students control over learning, boredom, gender, use of calculators, changing school calendar, lack of sleep, moving between schools, mathematics, drugs, pre-term birth weight, ability grouping, not labeling students, ability grouping for gifted students. The implications of this research finding can be the basis for improving more optimal learning strategies in higher education environments, especially IKIP Siliwangi.